Disorder policing to reduce crime: a systematic review - Braga, Anthony Allan (Campbell Systematic Reviews, 2019)
This Campbell systematic review examines the effects of disorder policing interventions on crime. The review summarizes evidence from 28 high-quality studies (representing 30 independent tests), including nine randomized controlled trials. Most the studies come from the United States.